PENYULUHAN HUKUM TENTANG PENGANGKATAN ANAK MENURUT HUKUM ISLAM DI DESA GANDATAPA, KECAMATAN KEDUNGBANTENG, KABUPATEN BANYUMAS - Priyadi, Aris; Suryati, Suryati; Anindito, Teguh (Universitas Wijayakusuma Purwokerto, 2025)
Marriage is an inner and outer bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on the belief in the Almighty God.